Kecukupan Gizi Pada Individu Dengan Penyakit Jantung Koroner Di RSUD Kota Salatiga - Frenscha Herclaudia Patrouw; Venty Agustina (Jurnal Keperawatan Muhammadiyah, 2021)
ABSTRACTCoronary heart disease is a condition in which the buildup of plaque in the heart arteries triggers a heart attack. This study aims to see the nutritional adequacy of individuals with coronary heart disease in Salatiga City Hospital. The research used a survey method. Respondents in this study were 100 individuals with coronary heart disease who live in Salatiga. Data collection techniques used anthropometric measurements, food frequency and food recall. The results of anthropometric and metabolic measurements showed that out of 100 individuals with coronary heart disease, 5 people (5%) lean body mass index (BMI), 19 fat (19%), 76 normal (76%) were obtained. Nutritional intake of 100 individuals with coronary heart disease using a 24-hour food recall showed that the average energy consumption was ± 1034.36 kcal, protein ± 38.92 g, fat ± 22.98 g, carbohydrate ± 167.11 g. Fulfillment of nutritional intake based on the adequacy category is mostly included in the weight deficit category, namely still energy (94 respondents), protein (78 respondents), fat (94 respondents), carbohydrates (94 respondents) but there are respondents who are in the good category, namely energy. (3 respondents), protein (4 respondents) fat (3 respondents), carbohydrates (3 respondents).  Keywords: Adequacy of Nutrition, Coronary Heart Disease, Salatiga